2021
DOI: 10.21608/svu.2021.70729.1119
|View full text |Cite
|
Sign up to set email alerts
|

Vinpocetine Suppresses Inflammatory and Oxidative Machineries in Acute Model of Inflammation—Pivotal Role of COX-2 Signaling

Abstract: The presence of inflammation is one of the key factors in the onset and progression of various medical disorders and diseases, making it a crucial challenge for treatment. The purpose of this study is to evaluate antioxidant and anti-inflammatory effects of Vinpocetine, using acute models of inflammation; Xylene-, Carrageenan (CGN)-induced inflammation and acetic acid-induced vascularpermeability in mice were used. We also employed molecular docking approach to verify the underlying mechanism of anti-inflammat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“… 109 Another study has reported that VNP restores natural skin morphology in carrageenan-induced paw skin, possibly by inhibiting tissue oedema, congestion, immune cell invasion, NF-κB expression, and the generation of detrimental inflammatory molecules comprising TNF-α, myeloperoxidase, COX-2, and prostaglandin (PGE)-2. 110 This agent also relieves pain associated with inflammatory conditions by eliminating NF-κB activation, paw skin cytokine generation, and cellular oxidative damage. 111 Additionally, the medication accelerates wound healing in diabetic rat skin and regenerates the skin's structural features, by decreasing epidermal thickness, renewing dermal granulation, and increasing collagen fibre formation.…”
Section: Discussionmentioning
confidence: 99%
“… 109 Another study has reported that VNP restores natural skin morphology in carrageenan-induced paw skin, possibly by inhibiting tissue oedema, congestion, immune cell invasion, NF-κB expression, and the generation of detrimental inflammatory molecules comprising TNF-α, myeloperoxidase, COX-2, and prostaglandin (PGE)-2. 110 This agent also relieves pain associated with inflammatory conditions by eliminating NF-κB activation, paw skin cytokine generation, and cellular oxidative damage. 111 Additionally, the medication accelerates wound healing in diabetic rat skin and regenerates the skin's structural features, by decreasing epidermal thickness, renewing dermal granulation, and increasing collagen fibre formation.…”
Section: Discussionmentioning
confidence: 99%